Family Values and ESG: Exploring Responsible Business Practices in Family Enterprises - Kansara, Dharmi (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Family-owned businesses, which are frequently driven by ingrained values, a long-term perspective, and close community ties, face both special opportunities and difficulties when it comes to implementing Environmental, Social, and Governance (ESG) practices as the world’s focus on sustainability and corporate responsibility grows. This study investigates the relationship between generational leadership, governance frameworks, and ethical business practices in order to determine how family values affect ESG engagement in family businesses. The study employs a mixed-methods approach, integrating qualitative insights from 12 in-depth interviews with family business leaders with quantitative data from 180 family-owned businesses across several industries. The results show that one of the main internal drivers of ESG behaviour is value alignment, particularly stewardship, legacy, and ethical responsibility. While founders frequently place a higher priority on social impact and informality, second- and third-generation leaders show a stronger preference for formal ESG practices, especially in environmental and transparency activities. Although many family businesses actively take socially and ecologically responsible acts, the study emphasizes that these efforts are frequently unreported or under documented, which restricts external recognition and access to resources relevant to ESG. Additionally, it has been demonstrated that formal governance structures like independent boards and ESG committees greatly improve ESG results. ESG adoption in family businesses is primarily motivated by principles rather than compliance, according to the study’s findings, and long-term effects depend on matching ESG frameworks with family business culture. Promoting ESG literacy, formalizing procedures without sacrificing principles, facilitating intergenerational cooperation, and offering policy-level assistance specific to family businesses are some of the main suggestions. This study offers useful strategies for incorporating ESG into the core of family company strategy and adds to the growing body of research on ethical business practices in family businesses.